(untitled) (SADGAMAYA, 2026)
Artificial intelligence (AI) and social media have become fundamental to daily communication, learning, and identity development. Among ten respondents aged 18–35, this qualitative research looks at how artificial intelligence driven content and social media usage affects mental health. Semi-structured interviews were analyzed using NVivo, revealing four major themes: emotional distress brought on by comparison and algorithmic pressure, digital addiction and decreased productivity, limited yet significant assistance from artificial intelligence tools, and privacy, authenticity, and misinformation issues. Word frequency visualization revealed dominant negative emotional expressions, and sensitivity study demonstrated a greater ratio of negative emotion than positive words. Although providing some advantages for connection and education, results generally indicate that AI and social media cause anxiety, stress, insecurity, and digital tiredness. The research stresses the need of digital well-being awareness, ethical artificial intelligence design, and better platform policies. More varied and bigger samples should be used in future research.